Illegal literature : toward a disruptive creativity - Roh, David S., 1978- (University of Minnesota Press, 2015)
"What is the cultural value of illegal works that violate the copyrights of popular fiction? Why do they persist despite clear and stringent intellectual property laws? Drawing on the disciplines of new media, law, and literary studies, Illegal Literature suggests that extralegal works such as fan fiction are critical to a system that spurs the evolution of culture. Reconsidering voices relegated to the cultural periphery, David S. Roh shows how infrastructure -- in the form of legal policy and network distribution -- slows or accelerates the rate of change. He analyzes the relationship between intellectual property rights and American literature in two recent copyright disputes. And, in comparing American fan fiction and Japanese dōjinshi, he illustrates how infrastructure and legal climates detract from or encourage fledgling creativity. Illegal Literature fills a crucial gap between the scholarly and the popular by closely examining several modes of marginalized cultural production. Roh makes the case for protecting an environment conducive to literary heresy, the articulation of an accretive rather than solitary authorial genius, and the idea that letting go rather than holding on is important to a generative creative process. In a media ecology inundated by unauthorized materials, Illegal Literature argues that the proliferation of unsanctioned texts may actually benefit literary and cultural development."--Publisher's website